2022
DOI: 10.1186/s40900-022-00339-9
|View full text |Cite
|
Sign up to set email alerts
|

iSelf-Help: a co-designed, culturally appropriate, online pain management programme in Aotearoa

Abstract: Introduction Current best practice recommends group-based pain management programmes for long-term improvements in persistent pain-related disability. However, there are barriers for people to access in-person delivered pain management programmes in Aotearoa. Aims To develop a co-designed, culturally responsive, online group-based pain management programme (iSelf-help) for people with persistent pain. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“… 51 In the three studies that focused on chronic pain among Indigenous Peoples, emphasis was on the endorsement of traditional health practices within treatment programs 53 and their placement within broader contexts of colonization, 54 as well as the development of a culturally responsive online pain management program. 55 Lastly, within the six studies that focused on chronic pain among people of color, some of the findings assessed the multiple dimensions of racialized discrimination 58 and highlighted the importance of culturally relevant online health education interventions, 42 culturally adapted physiotherapy, 57 and holistic interventions for addressing pain in light of the role of adversity on pain experiences. 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 51 In the three studies that focused on chronic pain among Indigenous Peoples, emphasis was on the endorsement of traditional health practices within treatment programs 53 and their placement within broader contexts of colonization, 54 as well as the development of a culturally responsive online pain management program. 55 Lastly, within the six studies that focused on chronic pain among people of color, some of the findings assessed the multiple dimensions of racialized discrimination 58 and highlighted the importance of culturally relevant online health education interventions, 42 culturally adapted physiotherapy, 57 and holistic interventions for addressing pain in light of the role of adversity on pain experiences. 45 …”
Section: Resultsmentioning
confidence: 99%
“…A large portion of the studies did not specify a theory or guiding conceptual framework ( n = 28, 41.7%). Of those studies that used a framework ( n = 39, 58.2%), examples include Black feminist thought and critical arts-based inquiry, 35 participatory action research, 55 Gadamerian philosophical hermeneutics, 36 two nested hierarchical models (Bronfenbrenner’s bioecological model and social ecological model), 16 the National Institute on Aging Health Disparities Research Framework, 31 Newman’s theory, 48 the sociology of illness experience, 60 Rhodes’ risk environment framework, 61 Bronfenbrenner’s process–person–context–time model, 46 Neuman’s systems model, 62 the life course perspective, 45 and the biopsychosocial model. 28 , 30 , 32 , 43 , 63 , 64 We noted that studies that drew on theory offered more fulsome understandings of and approaches to marginalization, which sheds light on the structures underpinning aspects of chronic pain experiences among marginalized groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has provided initial validation of a verbal and visual tool as a culturally appropriate and meaningful assessment instrument for Māori experiencing chronic pain, 23 and also supports recent adaptations to traditional pain management programmes and resources. 24 In other areas of health, culturally appropriate measures that have been designed for Māori include Hua Oranga (a measure of mental health outcomes), 25 Te Waka Kuaka (a needs assessment tool for traumatic brain injury) 26 and Mahi Oranga (a measure of occupational health). 27 Therefore, future research and funding should support the ongoing development of culturally appropriate and holistic pain assessment tools and treatments or work on adapting other relevant measures to be pain focussed.…”
Section: Kōrero Discussionmentioning
confidence: 99%
“…It affirms the value of building caring and inclusive learning communities. Studies have shown the need for culturally responsive pain management resources for people with persistent pain in New Zealand ( 201 , 209 ). The pain medicine curriculum would need to be flexible in design for it to be incorporated into the diverse landscape of medical education in Australia and New Zealand.…”
Section: Dimension 4: Supporting Institutional Delivery Of Pain Medic...mentioning
confidence: 99%